Legal Pluralism in Contemporary States: Between Traditional and Formal Justice Mechanisms in Nigeria and Côte d’Ivoire (Glocalism: Journal of Culture, Politics and Innovation, 2017)
It is generally assumed that African states have yet to explore the full potential of their traditional institutions and the specific role that society wants them to play in modern states. While focusing on Nigeria and Côte d’Ivoire, this empirical research seeks to explore legal pluralism in modern African democracy. The study specifically answers the research question: is the traditional justice system applicable to Nigerians and Ivorians in contemporary dispensation? The study finds out that a significant population at the grassroots rely on the traditional justice system, when compared with their counterparts in the cities. The rural population argues that the formal justice system is quite expensive and that the legal procedures are difficult to understand, coupled with the fact that court houses are mostly located in the cities. On the other hand, the gender-biased and male-dominated outlook of the traditional justice mechanism and its proneness to external influences, as well as the impact of modern religions, have continued to propel a considerable population (especially in urban areas) to patronize the formal justice system. Meanwhile, the adoption of western institutions of government by African states has forced traditional institutions to occupy the back seat. Hence, there is a mixed social environment wherein both formal and traditional justice systems are weak, and the states being weak themselves are significantly responsible for the weakness of traditional institutions. Consequently, flaws in both justice systems have compelled people to take the law into their own hands and to resort to jungle justice.
Keywords: traditional justice system; formal justice system; state; Nigeria; Côte d’Ivoire